Genetic and Epigenetic Impact of Chronic Inflammation on Colon Mucosa Cells - He, Jia; Han, Jimin; Liu, Jia; Yang, Ronghua; Wang, Jingru; Wang, Xusheng; Chen, Xiaodong (Frontiers in Genetics, 2021)
Chronic inflammation increases cancer risk, and cancer development is characterized by stepwise accumulation of genetic and epigenetic alterations. During chronic inflammation, infectious agents and intrinsic mediators of inflammatory responses can induce genetic and epigenetic changes. This study tried to evaluate both the genetic and epigenetic influence of chronic inflammation on colon mucosa cells. Repetitive dextran sodium sulfate (DSS) treatment induced chronic colitis model. Whole-exome sequencing (WES) (200x coverage) was performed to detect of somatic variations in colon mucosa cells. Using whole-genome bisulfite sequencing (BS) at 34-fold coverage (17-fold per strand), the methylome of both the colitis and control tissue was comparatively analyzed. Bioinformatic assay showed that there was no significant SNP/InDel mutation accumulation in colitis tissue, while did accumulated in aged mouse. 48 gene with SNP/InDel mutation was overlapped in the 3 colitis tissues, 2 (Wnt3a and Lama2) of which are in the cancer develop related signaling pathway. Differentially methylated regions (DMRs) assay showed that many genes in the colitis tissue are enriched in the cancer develop related signaling pathway, such as TGF-beta ans MAKP signaling pathway. Together, these data suggesting that even chronic inflammation did not obviously increase genetic mutation accumulation, it could both genetically and epigenetically alter some genes which related to cancer development.